Preliminary Analysis on Wall Beam Force Algorithms under the Action of Vertical Load - Gao, Yan Song; Sha, Yong (Applied Mechanics and Materials, 2012)
This paper makes a study on the stress state and internal force algorithms of wall beams under the action of vertical load. It also makes a comparative analysis to several typical wall-beam designs at present. Then, by using the finite element, it verifies the accuracy and reliability of internal force algorithm formulas of wall beams in current Code for Design of Masonry Structure, hoping to provide a solid theoretical reference for the selection of wall beam algorithm designs.